Integrasi Retorika Klasik dan Prinsip Qur’ani dalam Strategi Dakwah Islam Kontemporer - Rokibullah Rokibullah (Jurnal Impresi Indonesia, 2025)
Rhetoric has an important role in conveying religious messages effectively. In the Islamic tradition, rhetoric is not just the art of speaking, but part of a da'wah strategy that combines moral, emotional, and intellectual strength. In the digital era full of distractions and the demands of virality, many da'wah messages lose depth because they emphasize form rather than content. This research aims to examine the concepts of rhetoric and message theory in Islam, especially by examining the elements of ethos, pathos, and logos as well as the principles of communication of the Qur'an such as qaulan sadida, qaulan baligha, and qaulan layyina. With an integrative approach that combines classical rhetorical theory with Qur'anic communication principles in facing the challenges of contemporary da'wah. The method used is literature review with a qualitative-descriptive approach, through content analysis of literature from scientific journals, books, and classical and modern Islamic sources. The results of the study show that Islamic rhetoric emphasizes the balance between logic, emotion, and credibility of the message conveyor, as well as the importance of clarity, wisdom, and ethics in da'wah communication. The application of these principles is very relevant in answering the needs of da'wah in today's multicultural society and digital generation. In conclusion, Islamic rhetoric has great potential to strengthen the effectiveness of da'wah by prioritizing persuasive, ethical, and contextual messages in accordance with Islamic values.